2020
DOI: 10.34067/kid.0003942020
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Trial of Rifaximin Therapy for Lowering Gut-Derived Cardiovascular Toxins and Inflammation in CKD

Abstract: BackgroundRecent evidence suggests the systemic accumulation of by-products of gut microbes contributes to cardiovascular morbidity in patients with CKD. Limiting the generation of toxic bacterial by-products by manipulating the intestinal microbiota may be a novel strategy for reducing cardiovascular disease in CKD. Rifaximin is a minimally absorbed, oral antibiotic that targets intestinal pathogens and is commonly used as chronic therapy for the prevention of encephalopathy in patients with cirrhosis.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…On the other hand, rifaximin is commonly used for the treatment of irritable bowel disease and bacterial overgrowth, but its role in modulating gut microbial composition is still evolving. In prior non-cardiac studies, rifaximin did not alter the levels of cardiovascularly important microbial metabolites TMAO or SCFA, but did modulate gut microbial compositions [7][8][9]. These observations are largely consistent with the neutral findings from GutHeart, and may imply that better understanding of the targeted mechanisms may be necessary prior to the conduct of human intervention studies.…”
supporting
confidence: 70%
“…On the other hand, rifaximin is commonly used for the treatment of irritable bowel disease and bacterial overgrowth, but its role in modulating gut microbial composition is still evolving. In prior non-cardiac studies, rifaximin did not alter the levels of cardiovascularly important microbial metabolites TMAO or SCFA, but did modulate gut microbial compositions [7][8][9]. These observations are largely consistent with the neutral findings from GutHeart, and may imply that better understanding of the targeted mechanisms may be necessary prior to the conduct of human intervention studies.…”
supporting
confidence: 70%
“…Elevated deoxycholic acid levels can induce vascular calcification, which is connected with cardiovascular disease mortality. Deoxycholic acid is a biomarker of vascular calcification in patients with chronic kidney disease [ 40 , 41 ]. In addition, adenosine can induce hypertensive renal vasodilation by stimulating adenosine receptors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substances, which induce homeostatic changes in the intestinal microbiota or eubiosis are sometimes called eubiotics. Rifaximin–a poorly absorbed antibiotic lowered TMAO levels in mice [ 56 ] but in a randomized control trial in CKD patients failed to lower TMAO, p-cresol sulfate, indoxyl sulfate, kynurenic acid, deoxycholic acid, and inflammatory cytokines but did decrease bacterial richness and diversity [ 57 ]. A retrospective study that analyzed patients with hepatic cirrhosis found a reduced incidence rate of AKI and hepatorenal syndrome and a lower need for renal replacement therapy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%